Origin of the Great Nemunas Loops, South Lithuania - Baltrūnas, Valentinas; Šliaupa, Saulius; Karmaza, Bronislavas (Géographie physique et Quaternaire, 2005)
AbstractThe Nemunas River, one of the largest rivers of the Baltic region, is characterised by a generally straight valley. In the middle part of its course the Great Nemunas Loops are distinct features that occupy an area of 320 km2 near the Birštonas Resort. The Nemunas valley here is 1.5‑5 km wide and 45‑80 m deep. The loops are cut into a glaciolacustrine plain confined between glacial and deltaic relief complexes and formed during the two last phases of glaciation. The origin of the entrenched loops, as large as 6‑10 km, can not be explained in conventional terms of river meandering. The activity of underlying tectonic structures is the major factor, the Great Nemunas Loops being confined to the Birštonas tectonic depression. Despite their small magnitudes the neotectonic structures within the depression significantly influenced the glacial and meltwater sedimentation (hence, the topography) that controlled the geometry of the Nemunas valley. The initial sinuosity of the valley was only a little enhanced by later lateral erosion. Fault activity is indicated by numerous mineral water springs and straight channel segments. Only a few sites of similar mineral water discharge are documented in Lithuania, suggesting the specific structural setting of the Great Nemunas Loops. Inspection of drill cores revealed the inheritance of the Nemunas valley from underlying paleovalleys of Eemian and Holsteinian Interglacials, implying persistence of the controlling factors.